A New Age for Cancer Information Seeking: Are We Better Off Now? - Helft, Paul R. (Springer-Verlag, 2008)
ABSTRACT: A decade after the dawn of the Internet Age, are people who seek health information better off than they used to be? The current study by Arora and colleagues examines a small slice of the massive Health Information National Trends Survey dataset and attempts to understand the experiences of those US adults who have sought cancer information at any point in their lives from any source. One third reported that the information they encountered was hard to understand, and one half questioned the quality of the information they found. Several research questions regarding how individuals successfully find information on the Internet remain to be answered.